What One Hand Gives, the Other Takes: Industrial Countries' Policy Coherence for Development - Mendoza, Ronald U (Archīum Ateneo, 2007)
Rich countries' policies in areas such as trade, the environment, investment, migration, security, and technology could either bolster or blunt the effectiveness of their own aid policies to poor countries, depending on whether and to what extent all these policies are coherent or contradictory. Too often they are not coherent. But the main message of this author is that policy coherence for development cannot be determined by the rich industrial countries alone. Meaningful developing-country participation is essential in forming coherent, constructive policies.